Elevated Pentraxin-3 Concentrations in Patients With Leprosy: Potential Biomarker of Erythema Nodosum Leprosum - Mendes, Mayara Abud; de Carvalho, Daniel Serra; Amadeu, Thaís Porto; de Andrade Silva, Bruno Jorge; da Silva Prata, Rhana Berto; da Silva, Camila Oliveira; Ferreira, Helen; de Andrea Hacker, Mariana; Nery, José Augusto Costa; Pinheiro, Roberta Olmo; Sampaio, Elizabeth Pereira; Sarno, Euzenir Nunes; et al. (The Journal of infectious diseases, 2017)
High pentraxin-3 serum levels are presented in multibacillary leprosy patients with or without erythema nodosum leprosum (ENL) and distinguish them from healthy subjects and patients with reversal reactions. The article provides a new molecular target in ENL pathogenesis. Abstract Background Leprosy, the leading infectious cause of disability worldwide, remains a major public health challenge in the most severely affected countries despite the sharp decline in new cases in recent years. The search for biomarkers is essential to achieve a better understanding of the molecular and cellular mechanisms underlying the disease. Methods Pentraxin-3 (PTX3) analyses of sera from 87 leprosy patients with or without reactions were conducted via enzyme-linked immunosorbent assay. In situ identification of PTX3 in skin lesion was confirmed by quantitative reverse-transcription polymerase chain reaction, immunohistochemistry, and immunofluorescence assays. Results We found that PTX3 serum levels were higher in multibacillary patients when evaluated before the onset of acute erythema nodosum leprosum (ENL) and persistently elevated during reaction. Thalidomide treatment reduced PTX3 in the serum 7 days after starting treatment. In situ analyses have also demonstrated enhancement of PTX3 in ENL lesions and showed that treatment with thalidomide reduced its expression and the prominent neutrophilic infiltrate, a hallmark of the disease. Conclusions In summary, our study provides in vivo evidence that PTX3 is enhanced during ENL but not in reversal reaction and provides a new molecular target in ENL pathogenesis.